Autonomy and Well-Being in the Context of Cancer Care - O'Keefe, Katrina (2019)
This thesis investigates promotion of patient well-being and respect for patient autonomy within the context of cancer care. The thesis concludes that when designing treatments and screening methods, individuals working within the medical profession must consider how these treatments or screening methods can potentially impact on the well-being and autonomy of the patients using them. It is true that an individual’s health can impact their level of well-being, but the precise relationship between health and well-being is complex, and there may be more to consider when treating or screening a patient than the potential health benefits. The thesis begins by investigating what health is and the aims of medicine. One cannot understand what the relationship between health and well-being is without first having an understanding of what health is. The first chapter looks at different theories of health and finding them inadequate outlines a theory of health that fits well with our ordinary notions about health, helps us to make judgements about health and explains why we value health. The first chapter also looks at what the aims of medicine are and determines that the aims of medicine are not simply curative or restorative, but are also promotional and preventative. Moving forward the second chapter looks first at different types of theories of well-being. Then investigates the relationship between well-being and health on these different accounts; demonstrating that health and well-being have a complex relationship no matter which theory of well-being one chooses. Chapter three investigates autonomy and informed consent, arguing that informed consent is an expression of one’s autonomy and the moral significance lies within the autonomy of the person that is expressing their consent and not in the action of consenting. This thesis supports David Richards’ account of autonomy, which states that autonomy is a set of complex capacities that are possessed and expressed by the individual. The remaining two chapters look at end-of-life care and genetic screening for an inherited susceptibility to cancer. The chapter regarding genetic screening acknowledges the health benefits of early detection, but argues that screening of this type needs to take into consideration the impact the results may has on individual’s well-being and autonomy. While the chapter on end-of-life care argues that concept of a ‘good death’ that is supported through palliative care is incorrect because it is not flexible enough to ensure that the individual’s death goes well for them. Instead it argues that a ‘good death’ is one that promotes the individual’s well-being as much as possible and respects their autonomy for as long as possible. This allows that what makes a death go well for one person may not for another. Taking cues from these final chapters the thesis concludes that while the health of individuals is important, we need to take into consideration how different testing methods and treatments can impact people’s well-being and autonomy when we are designing them and offering them to people.